Diagnostic properties and classification of forest steppe soil The Vorona-Tsna interfluve of The Provolzhskaya upland - E. A. Levchenko; D. N. Kozlov; M. A. Smirnova; T. N. Avdeeva (Бюллетень Почвенного института им. В.В. Докучаева, 2017)
The first results of the study of soil cover patterns on the Tsna-Vorona interfluve of the Privolzhskaya Upland are presented. The poorly dissected topography and rocks with low filtration capacity predetermine the development of only semi-hydromorphic and hydromorphic variants of chernozems within the forest-steppe interfluve. These soils are formed under conditions of impeded surface and groundwater flows. Gley features were observed in the middle horizons even in the soils of the most drained areas, including eroded slopes of the ravines. The additional surface flow leads to the formation of albic material in the humus horizon and carbonate leaching beyond the lower boundary of the humus horizon at the depth of 20 cm and deeper. Texture- differentiated soils with different degrees of gleyzation are formed inthe depressions with a stagnant-percolative water regime. Iron-manganic concentrations and gley color patterns are detectedfrom the surface layers of the soilsformed in the non-drained parts of the interfluve with the groundwater table within the soil profile. The soil diversity, which was revealed during the detailed investigation of three key plots with contrasting moistening conditions, was subdivided into nine groups. These groups were named according to the substantive-genetic and factor-genetic classifications. The main difficulties in the genetic interpretation of soil morphological features were related to the seasonal and annual variability of atmospheric precipitation and additional surface and groundwater moistening and the accompanying elementary soil processes (metamorphic, eluvial, hydrogenic-accumulative, and illuvial-accumulative). The further development of soil classification for the forest-steppe zone depends on the improvement of the morphological and analytical diagnostic criteria of the soil water regime and water stagnationunder specific soil conditions, i.e., the intense coloring of the soil mass with humus and neutral reaction.